Genome dynamics of multidrug-resistant Acinetobacter baumannii during infection and treatment. Issue 1 (December 2016) - Wright, Meredith; Iovleva, Alina; Jacobs, Michael; Bonomo, Robert; Adams, Mark
Abstract Background Limited treatment options are available for patients infected with multidrug (MDR)- or pan-drug (PDR)-resistant bacterial pathogens, resulting in infections that can persist for weeks or months. In order to better understand transmission and evolutionary dynamics of MDRAcinetobacter baumannii (Ab) during long-term infection, we analyzed genomes from a series of isolates from individual patients at isolate-specific, patient-specific, and population levels. Methods Whole genome analysis of longitudinal isolates (range 2-10 isolates per patient spanning 0-829 days) from 40 patients included detection of single-nucleotide variants (SNVs), insertion sequence (IS) mapping, and gene content changes. Results Phylogenetic analysis revealed that a significant fraction of apparently persistent infections are in fact due to re-infection with new strains. SNVs primarily resulted in protein coding changes, and IS events primarily interrupted genes or were in an orientation such that the adjacent gene would be over-expressed. Mutations acquired during infection were over-represented in transcriptional regulators, notablypmrAB andadeRS, which can mediate resistance to the last line therapies colistin and tigecycline, respectively, as well as transporters, surface structures, and iron acquisition genes. Conclusions Most SNVs and IS events were isolate-specific indicating these mutations did not become fixed on the time scale investigated, yet over-representation of independent mutations in some genes or functional categories suggests that they are under selective pressure. Genome analysis at the population-level suggests that gene transfer including recombination also contributes to Ab evolutionary dynamics. These findings provide important insight into the transmission dynamics of Ab and the identification of patients with repeat infections has implications for infection control programs targeted to this pathogen.